GAMBARAN PENGETAHUAN REMAJA TENTANG SEKSUAL PRANIKAH DI SMA NEGERI 1 MEDAN TAHUN 2025 - Lestari Rahma; Aritha Br Sembiring; Wardati Humaira; Anisa Pebrianti Lubis (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Teenager is a crucial transitional phase in human life, marked by physical, emotional, and social changes, including the emergence of interest in sexual activity. A lack of knowledge about premarital sex can increase the risk of unhealthy sexual behavior. This study aims to describe the knowledge of teenager about premarital sex at 1 Senior High School Medan in 2025. This research used a quantitative method with a descriptive design. The study population included all 432 11th-grade students, and a sample of 208 students was selected using a purposive sampling technique. Data were collected using a questionnaire. The results showed that the majority of respondents had good knowledge of premarital sex, with 137 people (65.9%), followed by the sufficient category with 59 people (28.3%), and the poor category with 12 people (5.8%). Factors influencing teenager knowledge included information media, the role of parents, and peer influence. The conclusion of this study is that most adolescents at 1 Senior High School Medan have good knowledge of premarital sex. It is hoped that the school and parents will continue to play an active role in providing appropriate sexual education to improve knowledge and promote healthy and responsible sexual behavior among teenager.